Wood density and carbon concentration of decomposing stumps and coarse roots of European beech, Norway spruce and Scots pine - Steffen Herrmann; Steffi Dunger; Katja Oehmichen; Wolfgang Stümer (European Journal of Forest Research, 2025)
Root biomass contributes a significant proportion of total biomass and carbon storage in forest ecosystems. Deadwood (including dead roots) is an essential component of the ecosystem carbon (C) balance. Currently there are some shortcomings in the reporting of deadwood regarding the completeness and the level of detail. So far it is not possible to report about dead coarse roots since there is no existing data. Therefore, we assessed wood density and C concentration of excavated stumps and dead coarse roots (≥ 2 cm) of European beech ( Fagus sylvatica L.), Norway spruce ( Picea abies (L.) Karst .) and Scots pine ( Pinus sylvestris L.) in different stages of decay in a case study in Northeastern Germany. In total, 15 rootstocks – three for pine, four for spruce and eight for beech—could be excavated and analysed. The decay class (DC) belowground was found to be less advanced than the one aboveground in 60% of all cases where the DC above- and belowground differed. Significantly decreasing wood densities to a similar level in advanced DCs, i.e. DC 3 and 4, were observed with increasing DC for all tree species. DC has been found to be the main predictor of all variables tested; already explaining 83% of the variation in wood density as a single predictor. C concentration was highest in DC 4 for spruce and pine, but lowest for beech in the same DC. C concentration in beech was generally lower than in spruce and pine. Significantly increasing nitrogen (N) concentrations and decreasing CN ratios were observed with increasing DC for all tree species. Our results indicate that decomposing rootstocks i.e. coarse roots and stumps can be a significant sink (and source) of C. Based on this study—although it needs to be extended to more repetitions and sites in the future—a first estimation of the belowground deadwood C pool as part of the German greenhouse gas reporting can be conducted.

Harmonization and variation of deadwood density and carbon concentration in different stages of decay of the most important Central European tree species - Steffen Herrmann; Steffi Dunger; Katja Oehmichen; Wolfgang Stümer (European Journal of Forest Research, 2024)
Coarse woody debris (CWD) is a major component of the ecosystem carbon (C) balance. The estimation of C storage in CWD is an important element of the German greenhouse gas (GHG) reporting of forests, which is mainly based on the German National Forest Inventory. The deadwood C stock is calculated based on deadwood volume and, according to deadwood density (DD) and carbon concentration (CC) for each decay class (DC). Yet, the data basis of DD and CC per DC for above-ground CWD is still insufficient since there are very few country-specific measurements. Values from literature provide a first approximation for national-level estimates. However, different DC systems often prevent the use of DD and CC of other countries. Therefore, we developed a conversion method for harmonization of these data with the German four-class system. Following this, we conducted a meta-analysis to calculate mean DD and CC values for the main Central European tree species and to assess their variation. Significantly lower DDs were observed with increasing DC, except for beech between DC 3 and 4. Compared to spruce and pine, DD of beech CWD was significantly higher, overall as well as in DC 1 and 2. Species became similar in DD in advanced decay stages. A maximum of 92% of the variation in DD could be explained mainly by DC, CWD type, tree species and their interaction. DD values were mostly higher than current values in GHG reporting. CC increased with increasing DC in spruce and pine and was higher than in beech CWD, where no variation was detected. About 86% of the variation in CC could be explained mainly by DC, tree species and their interactive effect. The default value of 50% employed by the Intergovernmental Panel on Climate Change might under- (spruce, pine) and/or overestimate (spruce, pine, beech) the real CC depending on DC by up to 3.4 (pine) and/or 4.2% (beech). Based on our calculated mean DD and CC values, the accuracy of C stock assessment in deadwood as part of the GHG reporting for Germany can be substantially improved.

Diversity of dechlorination pathways and organohalide respiring bacteria in chlorobenzene dechlorinating enrichment cultures originating from river sludge - Pieter Vandermeeren; Steffi Herrmann; Danuta Cichocka; Pieter Busschaert; Bart Lievens; Hans-Hermann Richnow; Dirk Springael (Biodegradation, 2014)

Functional characterization of an anaerobic benzene‐degrading enrichment culture by DNA stable isotope probing - Steffi Herrmann; Sabine Kleinsteuber; Antonis Chatzinotas; Steffen Kuppardt; Tillmann Lueders; Hans‐Hermann Richnow; Carsten Vogt (Environmental Microbiology, 2010)
Summary The flow of carbon under sulfate‐reducing conditions within a benzene‐mineralizing enrichment culture was analysed using fully labelled [ 13 C 6 ]‐benzene. Over 180 days of incubation, 95% of added 13 C‐benzene was released as 13 C‐carbon dioxide. DNA extracted from cultures that had degraded different amounts of unlabelled or 13 C‐labelled benzene was centrifuged in CsCl density gradients to identify 13 C‐benzene‐assimilating organisms by density‐resolved terminal restriction fragment length polymorphism analysis and cloning of 16S rRNA gene fragments. Two phylotypes showed significantly increased relative abundance of their terminal restriction fragments in ‘heavy’ fractions of 13 C‐benzene‐incubated microcosms compared with a 12 C‐benzene‐incubated control: a member of the Cryptanaerobacter / Pelotomaculum group within the Peptococcaceae , and a phylotype belonging to the Epsilonproteobacteria . The Cryptanaerobacter/Pelotomaculum phylotype was the most frequent sequence type. A small amount of 13 C‐methane was aceticlastically produced, as concluded from the linear relationship between methane production and benzene degradation and the detection of Methanosaetaceae as the only methanogens present. Other phylotypes detected but not 13 C‐labelled belong to several genera of sulfate‐reducing bacteria, that may act as hydrogen scavengers for benzene oxidation. Our results strongly support the hypothesis that benzene is mineralized by a consortium consisting of syntrophs, hydrogenotrophic sulfate reducers and to a minor extent of aceticlastic methanogens.